Parish of Meunga, county of Cardwell - Queensland. Department of Mapping and Surveying (Brisbane : Dept of Mapping and Surveying, 1976)
Shows state and pastoral district, county and parish boundaries, land holdings and key to parishes within counties.
Also available online
Keywords: Real property -- Queensland -- Meunga -- Maps; Meunga (Qld.) -- Maps; Australian